Granulosa Cell Tumour and Associated Pyometra in an English Mastiff Female Dog - Khokhar, Vishal; Yadav, Dheeraj; Chaudhri, Sumer S.; Chandratre, Gauri A. (Indian Journal of Veterinary Sciences and Biotechnology, 2022)
Granulosa cell tumour (GCT) is the most common ovarian tumour which can affect 50% of the canine  population (Daleck and De Nardi, 2016).These tumors have  been categorized as sex cord-stromal tumors, which arise  from granulosa cell cords derived from atretic follicles  with higher occurrence in middle-aged dogs (Perez-Marin  et  al., 2014). The main clinical signs in GCT cases include  irregular estrous, vaginal bleeding, vaginal hyperplasia,  ovarian cyst, pyometra, vaginal prolapse and dermatological  lesions such as symmetric alopecia and hyperpigmentation  (Tavasoli and Solati, 2011; Perez-Marin et  al., 2014). Due to  very discrete clinical signs, the diagnosis of ovarian tumors  in dogs is usually complicated as it is occasionally confused  with other diseases. The histopathological examination is  essential for the confirmatory diagnosis of GCT (Matos et al.,  2019). This case report describes the occurrence of ovarian  granulosa cell tumor and associated pyometra in a female  dog presenting for clinical consultation and its diagnosis and  treatment.
Keywords: Granulosa Cell Tumour; Associated Pyometra; Female Dog